(untitled) (Carte Romanze, 2022)
Abstract: The paper provides the critical edition of one of the nine mythological Faules by Joan Roís de Corella, one of the key authors of the golden centuries of medieval Catalan literature. The fables, highlight of his prose production, represent a fundamental moment of Ovid’s reception in the Iberian context. Within them, the Parlament is the largest and perhaps the richest in interesting aspects. It is a ‘convivio ’ in which the author participates, in the fictitious role of ‘coronist ’, director and transcriber, and five members of the Valencian elite who narrate (‘recite’) five myths. Two of which are particularly dear to the Romance literary civilization: the myth of Narcissus and that of Philomena. Structured as a ‘convivio’, the text testifies to a way of living-sharing literature concretely, albeit in a fictitious way. An example of ‘agita’ literature, in perfect ‘eutrapelic’ harmony, between chosen friendships; who spend each other in an exercise of ‘alt and gentil estil’, who are moved by listening to each other, who share the compassion for unhappy loves and the reproach for illicit ones. A text which, due to its convivial frame, anchors itself to the classical and medieval models of symposium literature, and, at the same time, places itself on the trajectory that leads to the Renaissance ‘civil conversation’. The Introduction illustrates its peculiarities, namely dialogic structure, literary references, aesthetic–ideological coordinates. Then, the Text is provided, basically reconstructed on the lesson of the ms. R. 14.17 of Trinity College, which is accompanied by a foot page annotation corpus to give account of the amendments, to highlight the variants of the ms. Maians 728, also significant as possible variants of the author, and to report the cases of divergence of reading with respect to previous editions. Finally, the Apparatus and the Bibliography follow.